If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5a + 1 = 6a Reorder the terms: 1 + 5a = 6a Solving 1 + 5a = 6a Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-6a' to each side of the equation. 1 + 5a + -6a = 6a + -6a Combine like terms: 5a + -6a = -1a 1 + -1a = 6a + -6a Combine like terms: 6a + -6a = 0 1 + -1a = 0 Add '-1' to each side of the equation. 1 + -1 + -1a = 0 + -1 Combine like terms: 1 + -1 = 0 0 + -1a = 0 + -1 -1a = 0 + -1 Combine like terms: 0 + -1 = -1 -1a = -1 Divide each side by '-1'. a = 1 Simplifying a = 1
| 3(5+3x)=x-3 | | 4y-x+10=3y | | 7x+3y-4x-8y= | | 9x-11=5x+3+18 | | 4x-y+10=3x | | 1+kx=3x^2+5x+13 | | 5x^2+53x+30=30 | | x(5-k)=12 | | 5x+89=11x-13 | | 3x+4+11x-6=180 | | 3x^2-16x+15=0 | | f(x)=4x^2-5 | | -120/(-10)= | | 12x-20=6x+29+35 | | 6x+93=12x-9 | | 12x-9=9x+9 | | 2x^7= | | 2m+7=5m-5 | | 5(6x+1)=305 | | 109-5x=22x+22 | | 13x+24=9x+56 | | 4ab(2a+b-c)= | | =(8m+7)((64(m*m))-56m+49) | | 9x+6=12x-15 | | 11x+11=4x+4+77 | | 13x-10=9x-15+33 | | 6[3a-3a(3a+3b)+9a^2]= | | (-6m^6n^2)(7mn^4)= | | 9x-15=13x-10+33 | | 0.01w=-0.045 | | 4x+8=90-4x | | (-2m^4n^5)(7mn^3)= |